2022
DOI: 10.3389/fneur.2022.872927
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Genetic Spectrum of Patients With Clinically Suspected Hereditary Progressive Spastic Paraplegia

Abstract: Background and PurposeA variety of hereditary diseases overlap with neurological phenotypes or even share genes with hereditary spastic paraplegia (HSP). The aim of this study was to determine the clinical features and genetic spectrum of patients with clinically suspected HSPs.MethodsA total of 52 patients with clinically suspected HSPs were enrolled in this study. All the patients underwent next-generation sequencing (NGS) and triplet repeat primed PCR to screen for the dynamic mutations typical of spinocere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…In addition to the pattern of inheritance, differences related to the phenotype of cases may also have influenced the results, since 53.7% of our cohort had complex phenotype. A study carried out in China presented similar results to ours, having evaluated 52 families, 39 of them with a complex phenotype, 18 reinforcing this possibility.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to the pattern of inheritance, differences related to the phenotype of cases may also have influenced the results, since 53.7% of our cohort had complex phenotype. A study carried out in China presented similar results to ours, having evaluated 52 families, 39 of them with a complex phenotype, 18 reinforcing this possibility.…”
Section: Discussionsupporting
confidence: 84%
“…As a semiquantitative molecular technique, multiple ligation-dependent probe amplification (MLPA) is typically performed to detect abnormal CNVs escaping detection by conventional polymerase chain reaction (PCR) amplification sequencing, which has been widely applied in hereditary diseases caused by chromosome abnormalities, gene fragment deletions or rearrangements, such as Duchenne muscular dystrophy/ Becker's muscular dystrophy, spinal muscular atrophy, and HSP. [11][12][13][14] Although various HSP subtypes have been reported and studied elaborately, [15][16][17][18][19] information on the pattern in the HSP subgroup with rearrangements has yet to be fully defined, leading to a vague distinction between point mutation-and rearrangement-related groups. Here, we applied a combination of WES with MLPA to explore the genotype-phenotype correlations as well as the landscape and hallmarks of a Chinese cohort of 270 HSP patients.…”
mentioning
confidence: 99%
“…However, Japan Spastic Paraplegia Research Consortium (JASPAC) reported a 1% frequency of SPG8 analyzing 206 Japanese AD-HSP families, and a study from China on 52 patients with clinically suspected HSPs reported one patient with SPG8 (c.1725T>A p.N575K). [ 5 , 6 ] Ginanneschi et al . [ 7 ] (2020) from Italy reported four new mutations in the KIAA0196 gene.…”
mentioning
confidence: 99%